The Effect of Spinal Anesthesia as a Risk Factor for Low Back Pain in Women after Cesarean Section - Homayoun Tabesh; Seyed Bahram Seif; Farnaz Farrokhnia; Majid Rezvani; Ariyan Tabesh (مجله دانشکده پزشکی اصفهان, 2017)
Background: We planned a study to investigate the effect of spinal anesthesia in producing low back pain (LBP) in women following Cesarean section.